International airline alliance network design with uncertainty - Yang, Wendong; Shao, Jiajia; Jiang, Yun; Xu, Zhengjia; Tsourdos, Antonios (MDPI, 2021)
This paper addresses the alliance route network design problem considering uncertainty in the unit transportation cost. An alliance route network was constructed based on a hub-and-spoke (HS) network, in which airlines could achieve inter-area passenger transport through their international gateways. The design problem was formulated with a robust model containing a set of uncertain cost parameters. The model was established based on a three-subscript model of an HS network. A case study with real-world data was used to test the proposed model. The results showed that this robust solution can reduce the impact of cost uncertainty
Keywords: robust model; hub-and-spoke network; network design; alliance route network